(untitled) (MAUSAM, 1997)
ABSTRACT. The differences in the averages of surface temperature and rainfall during the periods 1931-60 and 1961-90 are studied for 166 individual stations covering major parts of India. To test the significance of the difference, student’s ‘t’ test has been applied. The fall in air temperatures in the north Indian stations is mainly due to the significant fall in minimum temperatures and rise in air temperatures in the south Indian stations is due to the significant rise in maximum temperatures. No significant change is observed in rainfall. However, over hill stations the rainfall has decreased and over urban/industrialized cities the rainfall has increased.